Ritual Dalang Dalam Dharma Pewayangan Di Kecamatan Tampaksiring Kabupaten Gianyar - I Nyoman Trisna Jaya; I Ketut Donder; Ni Komang Sutriyanti (Kamaya: Jurnal Ilmu Agama, 2018)
Puppeteer ritual is a religious activity done by puppeteer in every shadow puppet show in accordance to ethics written in Dharma Pewayangan. Puppeteer ritual has complex functions and philosophy values which have not been reviewed deeply. The thesis entitled “Puppeteer Ritual in Dharma Pewayangan in Tampaksiring, Gianyar Regency” was a result of puppeteer ritual in a shadow puppet show. This research was very significant to be done in order to understand the functions and values lied in the ritual. This research promoted 3 issued, namely: 1). The means needed by the puppeteer for the ritual, 2). How the ritual process in accordance to Dharma Pewayangan, 3). How the implication of the implementation in accordance toDharma Pewayangan. In general, this research aimed to identify the existence and role of puppeteer ritual in Balinese shadow puppet show. In particular, this research aimed to explain values contained in the puppeteer ritual. This research was designed as a qualitative research using some theories such as: religion theory and semiotic theory. The data collection methods used covered observation, interview, documentation, and literature review. All data collected were processed using interpretative descriptive technique. The result of the research shows that means of the ritual in shadow puppet show was divided into 2 parts, namely: performance apparatus and ritual means in the show. The ritual process done by the puppeteer before, during, and after the shadow puppet show was always accordance to ethics written in lontar dharma pewayangan. The implementation implication of the ritual done by the puppeteer in the shadow puppet show covered theology, religious, culture, and aesthetic implication. This research proved that the ritual done by the puppeteer in shadow puppet show was not only a word and act, but also a must in accordance to ethics written in dharma pewayangan.